Multiyear sea ice thermal regimes and oceanic heat flux derived from an ice mass balance buoy in the Arctic Ocean. Issue 1 (22nd January 2014) - Lei, Ruibo; Li, Na; Heil, Petra; Cheng, Bin; Zhang, Zhanhai; Sun, Bo
<x xml:space="preserve">Abstract</x> [1] The conductive and oceanic heat fluxes and the mass balance of sea ice were investigated utilizing an ice mass balance buoy (IMB) deployed in the Arctic Ocean. After IMB deployment, the ice thinned from 1.95 m in late August to 1.46 m by mid‐October 2008. From then on, ice growth until mid‐June 2009 increased the ice thickness to 3.12 m. The ice temperature and consequently the conductive heat flux at the ice surface exhibited persistent high‐frequency variations due to diurnal and synoptic‐scale atmospheric forcing. These signals propagated downward with damped magnitude and temporal lag. The competition of oceanic and conductive heat flux dominated the low‐frequency variations of ice growth. However, high‐frequency variations in ice growth were controlled largely by the oceanic heat flux. From mid‐November 2008 to mid‐June 2009, the average oceanic heat flux along a track from 86.2°N, 115.2°W to 84.6°N, 33.9°W was 7.1 W/m2. This was in agreement with that derived from an IMB deployed in 2005, about 1.5° to the north of our buoy. We attributed the relatively high oceanic heat flux (10–15 W/m2) observed during autumn and early winter to summer warming of the surface ocean. Upward mixing of warm deep water, as observed when our buoy drifted over the shallow region of the Lomonosov Ridge (85.4°–85.9°N, 52.2°–66.4°W), demonstrated the impact of bathymetry on the oceanic heat flux under ice cover, and consequently on the basal ice mass balance.